Analysis of air humidity and temperature for post lightning circumstances - Tuan Othman, Sharifah Sakinah; Jasni, Jasronita; Mohtar, Mohd Nazim (Universiti Putra Malaysia Press, 2017)
Lightning is a natural phenomenon that generates a high electric field during thunderstorm. It has been reported that lightning strikes amid storms can occur around 100 times per second. The atmospheric electric field is an imperative parameter during a thunderstorm. Therefore, monitoring the electric field and its parameters is the best way for local lightning forecast. The electric field monitoring data can validate the accuracy of weather prediction in a local area from meteorology department or by using equipment specially designed to measure this electric field that exists when the phenomenon of lightning occurs. In this paper, the relationship between lightning, air humidity and temperature is discussed to understand the post lightning effect on these electric parameters. Additionally, the characteristics of the parameters are observed and analysed.